Kritik atas Kritik al-Fadi terhadap Gramatikal al-Qur’an - Hasan Ansori (Universitas Darussalam Gontor, 2019)
Charging an authenticity of al-Qur'an is not something new in the realm of ‎Qur’anic studies. They who criticize al-Qur’an seemed to think that they were able to find ‎out an error in al-Qur'an. In fact, there is no single accuse toward al-Qur'an lasts long ‎nowadays. One who was known criticize al-Qur’an was ‘Abdullah ‘Abd al-Fadi, a Saudi ‎Muslim wrote book ‘Is the Qur'an Infallible?’ Al-Fadi was very confident and defiance to ‎say there were 243 errors in the Qur'an so that al-Qur’an is not as sacred as most Muslims ‎believe in. In his book, al-Fadi mentions ten topics discussing errors he found in al-‎Qur'an, including grammatical errors in Qur’anic language. By reviewing al-Fadi's work, ‎this paper presents several examples of errors stated by al-Fadi, coming with an attempt to ‎counter them by referring to ideas of Muslim scholars, especially grammatical experts and ‎interpreter (mufassir). This paper conclude that al-Fadi's charge is not true. All the ‎grammatical errors of the language put forward by al-Fadi can be refuted through proper ‎grammatical argumentation and it seems that al-Fadi did not understand the Arabic rules ‎properly before indicating errors of Qur’anic grammar before accusing it.‎